2020
DOI: 10.1111/maq.12620
|View full text |Cite
|
Sign up to set email alerts
|

Interventive Care: Uncertainty, Distributed Agency, and Cesarean Section in a Zika Virus Epidemic

Abstract: Beginning in 2015, Brazil witnessed the births of thousands of children with neurological abnormalities linked to the Zika virus. Drawing on ethnographic fieldwork conducted between 2016 and 2018 with parents of children with congenital Zika syndrome in Salvador da Bahia, this article attends to how one of Brazil's most overused obstetric technologies—cesarean section—was mobilized to mitigate the uncertainties of Zika's reproductive consequences. I argue that during the epidemic, C‐section constituted a form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In addition, research focusing on information seeking behaviors during the Zika pandemic found that attempts to resolve uncertainties included turning to authoritative sources of medical information (such as family doctors, national ministries of health and national public health institutions, and international organizations), but also to information from friends and family [ 54 , 55 ]. Focus group participants from all four countries showed similar information-seeking behaviors, yet our analysis suggests that such efforts to resolve uncertainties are hampered by two interrelated types of uncertainties: First, information-seeking was complicated by what we call information uncertainty, notably by the high amount of available information – or what the WHO calls an “infodemic” [ 56 ]– and the dynamic changes of regulations and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research focusing on information seeking behaviors during the Zika pandemic found that attempts to resolve uncertainties included turning to authoritative sources of medical information (such as family doctors, national ministries of health and national public health institutions, and international organizations), but also to information from friends and family [ 54 , 55 ]. Focus group participants from all four countries showed similar information-seeking behaviors, yet our analysis suggests that such efforts to resolve uncertainties are hampered by two interrelated types of uncertainties: First, information-seeking was complicated by what we call information uncertainty, notably by the high amount of available information – or what the WHO calls an “infodemic” [ 56 ]– and the dynamic changes of regulations and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research focusing on information seeking behaviors during the Zika pandemic found that attempts to resolve uncertainties included turning to authoritative sources of medical information (such as family doctors, national ministries of health and national public health institutions, and international organizations), but also to information from friends and family [24,25]. Focus group participants from all four countries showed similar information-seeking behaviors, yet our analysis suggests that such efforts to resolve uncertainties are hampered by two interrelated types of uncertainties: First, information-seeking was complicated by what we call information uncertainty, notably by the high amount of available information -or what the WHO calls an "infodemic" [26]-and the dynamic changes of regulations and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropologists have attended to the ways in which notions of plasticity shape bodily practices in Brazil, from popular and religious healing to biomedicine, Indigenous and Afro‐Brazilian ceremonies to cosmetic plastic surgery (Béhague 2016; Edmonds 2010; Jarrín 2017; Rabelo 2014; Sanabria 2016; Vilaça 2005; Williamson 2021). While some have emphasized how biomedical therapeutic technologies like disaggregated, synthetic birth‐control hormones, become modalities of self‐care, bodymind enhancement, and even social mobility, scant attention has been paid to technologies of (re)habilitation for children, much less for disabled children (cf.…”
Section: Habilitating Bodyminds Caring For Potentialmentioning
confidence: 99%